Evaluating maternal mortality ratios of Nepal with 2003 Nepal world health survey estimates - Bhandary, Shital (Journal of General Practice and Emergency Medicine of Nepal, 2018)
Introduction: Maternal mortality is an important indicator for women’s health. It is estimated as pregnancy related maternal mortality ratio (PRMR) in Nepal Demographic and Health Surveys (NDHS). However, 2011 National Population and Household Census (NPHC) gave a very high estimate of this indicator and challenged the 1996 and 2006 NDHS estimates. This warrants the evaluation of these estimates using another reliable source and this study aims to fill that gap. Method: The 2003 Nepal World Health Survey (WHS) data files were used to get PRMR for 1995-2002. SPSS syntax was used to create sibling history to compute PRMR for the country. Standard error was computed to get 95% confidence interval (CI) and compare it with NDHS and NPHC estimates. Result: Data quality of sibling history was found to be reliable for getting maternal mortality estimates as age and age at death data was good. Adjusted PRMR of 285 was obtained for 1996-2002 with 95% CI of 161-391. This CI overlapped for 2006 NDHS estimate but it did not overlap the 1996 NDHS and 2011 NPHC estimates. Conclusion: PRMR from 2003 Nepal WHS were found to be consistent with 1996 and 2006 NDHS as per reported confidence intervals but it was not consistent with the 2011 NPHC estimate. As NPHC used indirect method due to poor data quality of observed deaths and live births, it cannot be considered as a reliable estimate of PRMR. Thus, it is recommended to use surveillance based methods to get valid and reliable estimate of PRMR and MMR for Nepal.